The collection-based inventory and spatial analysis of Hieracium s.str. (Asteraceae) in Finland - Alexander Sennikov (Biodiversity Data Journal, 2025)
Due to the lack of complete taxonomic inventories and revisions for nearly 120 years and a high number of chaotic and conflicting species descriptions in the times of the primary biodiversity exploration, the actual diversity of apomictic species of Hieracium in Finland is currently unknown. The existing nomenclatural and bibliographic inventory, published in 2002, does not include taxonomic evaluations. To compensate for this deficiency, there is an urgent need for a new taxonomic revision. The operative foundation for this revision is an inventory of the taxonomic diversity and distribution patterns on the basis of primary sources, i.e. herbarium collections identified by major taxonomic authorities.A complete checklist of Hieracium species occurring in Finland, which were accepted in major authoritative sources (recently or in the past) and identified in herbarium collections, includes 137 accepted species, which are deemed mostly apomictic. These taxa are considered taxonomically evaluated and are recommended for current use in national checklists and manuals. Brief species descriptions are provided as the basis for a new identification key. Species distributions in Finland are recorded on the basis of herbarium specimens according to the traditional biogeographic provinces of Eastern Fennoscandia. The distribution patterns revealed in the hierarchical cluster analysis highlight a largely isolated position of the Åland Islands, with strong phytogeographical connections to Sweden; the presence of taxa with strictly oceanic distributions in south-western Finland; and a high level of taxonomic dissimilarity between the north (Lapland and neighbouring territories) and the east (southern and central mainland Finland and neighbouring territories) of Finland. The eastern floristic element is considered autochthonously developed in Finland during the postglacial colonisation of Northern Europe by Hieracium plants and contains numerous endemics or near-endemics of the country. Two species are established aliens, which were introduced as park ornamentals over 100 years ago. A new synonymy is established: Hieracium schmidtii subsp. residuum is reduced to a synonym of H. crinellum; its only record in Finland is a local relic of the postglacial period, remotely isolated from the main populations in Norway and southern Sweden. Numerous further province-level and country-level records are expected in Finland in the course of a new taxonomic revision, with a total to reach or exceed 200 species.